2017
DOI: 10.1111/1440-1630.12379
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Competency Standards for Occupational Therapy Driver Assessors: An overview of the evidence for the inclusion of cognitive and perceptual assessments within fitness‐to‐drive evaluations

Abstract: This overview of systematic reviews supports the inclusion of assessment of a range of cognitive and perceptual skills as key elements in a comprehensive driver assessment and therefore should be included in the revised competency standards for occupational therapy driver assessors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Occupational therapy driver assessor practice across Australia is diverse, with a review of off-road assessments including 20 tests that may be completed by occupational therapists (Unsworth et al, 2005). A recent overview by Fields and Unsworth (2017) summarised the evidence for including cognitive and perceptual assessments within occupational therapy driver assessments, recommending multiple components of cognition and perception are assessed, which was supported in the results in phase 1 (Quote 4) and has been incorporated into the revised competency standards. Both phases identified that the timing and types of assessments and processes undertaken are related to the context and jurisdiction in which the occupational therapy driver assessor practises, and the training course undertaken.…”
Section: Flexibility and Clinical Reasoningmentioning
confidence: 99%
“…Occupational therapy driver assessor practice across Australia is diverse, with a review of off-road assessments including 20 tests that may be completed by occupational therapists (Unsworth et al, 2005). A recent overview by Fields and Unsworth (2017) summarised the evidence for including cognitive and perceptual assessments within occupational therapy driver assessments, recommending multiple components of cognition and perception are assessed, which was supported in the results in phase 1 (Quote 4) and has been incorporated into the revised competency standards. Both phases identified that the timing and types of assessments and processes undertaken are related to the context and jurisdiction in which the occupational therapy driver assessor practises, and the training course undertaken.…”
Section: Flexibility and Clinical Reasoningmentioning
confidence: 99%
“…All occupational therapists have ethical obligations to address all aspects of community mobility, including driving (Fields & Unsworth, 2017;Occupational Therapy Australia, 2015). Previous research to address driving within non-OTDA practice has identified gaps in clinical competence among Canadian clinicians (Korner-Bitensky et al, 2010) and reduced confidence among Irish and American clinicians Stack et al, 2018).…”
Section: | Introductionmentioning
confidence: 99%
“…Strategic decisions are made before driving commences, whereas tactical and operational decisions require information about the immediate driving situation and are thus made in real time. The interaction of several cognitive abilities is required, especially at the tactical level, for which the most important factors for predicting motor vehicle collisions have been found to be executive function; focused, sustained, divided and selective attention; visuospatial function; decision-making; processing speed and memory (Field and Unsworth, 2017; Hird et al., 2016; Lafont et al., 2008; Seong-Youl et al., 2014). The planning or strategic level is the most difficult level to assess in a standardised way, because it concerns mainly evaluation of the risks involved and avoiding risks before the driver sits behind the wheel.…”
Section: Introductionmentioning
confidence: 99%